KADIWANIHAN a sustainable, resilience-generative, hostel, market and evacuation sanctuary - Dianzon, Michaela Sophia P.
This architectural comprehensive design project aims to address three major issues in the Philippines - inadequate disaster risk management, lack of permanent market spaces for the Kadiwa program, and unavailability of transient homes for low-income households. The proposed solution involves using architecture to combine three different typologies to solve these problems. The common spaces of evacuation centers will be explored to create a spatial configuration that is adaptable to all typologies and readily available to the barangay and nearby communities. The study will focus on Barangay Pasong Tamo in Quezon City, which currently houses most of the existing evacuation sites in the city. Special attention will be given to providing a green transition to promote energy-saving impact and self-sustainability within the area. The proposed design will utilize bioclimatic architecture to maximize thermal comfort through passive cooling and optimal lighting conditions. The design will also integrate architectural psychology elements to help with stress and trauma mitigation for disaster victims. The combination of these typologies will help improve the country's current disaster risk management and mitigation principles while bringing food closer to the communities. This approach will help people reduce transportation costs with lower market prices. The proposed typology will benefit both the community and the environment.